SEXUAL ACTIVITY AND VAGINAL DOUCHING WITH THE INCIDENCE OF GONORRHEA IN THE LOCALIZATION OF BADUNG AND BULELENG BALI INDONESIA - cindy meilinda sari; Ketut Putra Sedana (MIDWINERSLION : Jurnal Kesehatan STIKes Buleleng, 2018)
ABSTRACT Backgorund: Gonorrhea infection in Indonesia ranks highest among all types of sexually transmitted disease.Cases of sexually transmitted Infections diseases continue to increase, the phenomenon of an increased and spreading case of sexually transmitted Infections that occur in high risk group so quickly, one of the high risk group are women sex workers. Vaginal douching increases the risk of sexually transmitted disease. Another problem that sexually transmitted infectious diseases have the potential increases the risk of HIV transmission through sexual intercourse which became a global problem. Objective: analyze the effect of sexual activity and vaginal douching with incidence of gonorrhea. Method: Observational case control starts with identifying the outcomes of case Group (women sex worker with gonorrhea) and the control group (women sex worker not infected gonorrhea). Results: The results of the multiple logistic regression statistic in the case to the control shows that the variables that influence the occurrence of gonorrhe (value of p < 0.05) on control is: how sexual intercourse with more than two categories (OR = 2.5; 95% CI = 0.8 – 5.5). Conclusion: The most influential Way sexual relationship affect the occurance of gonorrhea